Social Engineering Approach to Manage Social Environmental Dispute Impacted by Development Plan (Case Study of Floating Storage Regasification Unit/FSRU Development Plan) - Endang Susilowati; Zaenal Arifin; Sukriyah Kustanti Moerad (Jurnal Sosial Humaniora, 2019)
One of the strategic issues in the 2016-2030 SDGs (Sustainable Development Goals),the 7th (seven) goal is clean and affordable energy. The social engineering approach inthe social-environmental dispute management of the affected community is an appliedresearch from the case study of the Pasuruan FSRU development plan, namelybuilding floating LNG storage and supporting facilities and facilities at sea, subseapipeline construction located in the Madura Strait, in the north of the RegencyPasuruan and Sidoarjo Regency, as well as deploying land pipes in Permisan Village,Tambak Kalisogo, and Kupang, Jabon District-Sidoarjo Regency. This research is adescriptive analysis study, which is carried out with cross-sectional, in the study area.The data used in this study are primary and secondary. The primary data fromparticipants in socialization activities of development plan were 33 respondents inSidoarjo Regency and as many as 25 fishers respondents in Pasuruan City andRegency. Besides, the primary data from the questionnaire to 101 residents affected byland pipeline deployments and 29 people, fishing communities, joined in the HNSI inPasuruan Regency and City. Often the development plans are hampered by theimplementation, including strategic development plans, such as deploying fuel/oil andgas pipes, refineries, FSRUs, etc. due to the issue of dispute in the social environment.This study aims to support ongoing development activities, to underpin decisionmaking policies. The results of the study show that the community perception factor isvery significant towards the development plan that must be managed. Management ofthese problems is a social engineering approach at the planning stage in thedevelopment process by involving various stakeholders ranging from the centralgovernment, local government, related agencies, NGOs, local figures, andcommunities affected by the development.